Fog based service oriented IOT infrastructure - Heya, Tasnia Ashrafi; Arefin, Sayed Erfan; Joy, Kowshik Dipta Das; Hossain, Md. Arshad (BRAC University, 2017)
Cataloged from PDF version of thesis report.